Autism spectrum disorder in children and young people with non-epileptic seizures. (December 2019) - McWilliams, Andrew; Reilly, Colin; Gupta, Jaya; Hadji-Michael, Maria; Srinivasan, Ramya; Heyman, Isobel
Highlights: Assessment of non-epileptic seizures should include detailed screening for autism. Assessment of epilepsy in autism should involve considering non-epileptic seizures. Possible reasons for an association between NES and ASD are discussed. Abstract: Purpose: Non-epileptic seizures are paroxysmal events which to an observer resemble epileptic seizures. Proposed risk factors incorporate biopsychosocial aspects including factors in the affected individual. Unexpectedly high rates of autism spectrum disorder (ASD) occurred in the clinical population reported here. Although elevated levels of psychiatric co-morbidity are known to be present in patients with NES, ASD has only been previously described in a single case report. Methods: This case series captures rates of ASD in 59 children and young people who were referred to a specialist paediatric mental health service at Great Ormond Street Hospital, London, UK for assessment and treatment of non-epileptic seizures between 2012 and 2016. Results: 10/59 (16.9%) of the children and young people with non-epileptic seizures also had ASD, with 5/10 (50%) of these undiagnosed with ASD before referral. Children and young people with ASD were significantly more likely to have tics or attention-deficit hyperactivity disorder than those without ASD. Conclusion: ASD may be a common co-morbidity in non-epileptic seizures. Careful clinical assessment with consideration of ASD traits is therefore important in the non-epileptic seizures population. It is beneficial to diagnose ASD early as its presence is likely to require a modified approach to assessment and treatment of non-epileptic seizures. Study of the development of non-epileptic seizures in ASD may suggest hypotheses for the pathogenesis of non-epileptic seizures in the wider population.